KAJIAN VARIABILITAS GALUR-GALUR PADI GOGO PADA LAHAN KERING MASAM - Angelita P L; Rini Hermanasari; Yullianida Yullianida; Aris Hairmansis (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2020)
[VARIABILITY STUDIES OF UPLAND RICE LINES ON AN ACIDIC SOIL]. Suscessful upland rice breeding program to produce productive and adaptive to acid soil is dependent upon the extent of genetic variability of the breeding materials. Objectives of this study were to estimate the genetic variability, phenotypic and genotypic coeficient of variations, heritability, genetic advance, and correlation of five traits observed from dari 298 upland rice lines and five checks varieties. A field field experiment arranged in an augmented design was conducted at the Tamanbogo Experimental Station in Lampung 1 MT 2019.. The results of the analysis of variance showed that there was diversity among lines, resulting in differences in appearance on plant height, number of productive tillers, and yields. High heritability, genetic advancement, and high correlation on the number of productive tiller indicate that this character is a selection criteria so that selection can be done in an effort to improve these characters